Comparing Cognitive Learning Outcomes as the Impact of ADI-S and ADI Learning Models with Different Scientific Reasoning Abilities - Rena Amelia; Endang Budiasih; Yahmin Yahmin (Pascasarjana Universitas Negeri Malang (UM), 2020)
Abstract: This aims of the study to compare the cognitive learning outcomes of students who learned with Argument Driven Inquiry-Scaffolding (ADI-S) and Driven Argument Inquiry (ADI) with different scientific reasoning abilities. This research is a quasy experimental design. The instruments were used cognitive learning outcomes test and the test of scientific reasoning abilities. Data were analyzed using two way ANCOVA (2x2 factorial). The results showed: (1) learned with ADI-S on the reaction rate material get cognitive learning outcomes higher than learned with ADI, (2) student with high scientific reasoning abilities have better cognitive learning outcomes rather student with low scientific reasoning abilities both in ADI-S’s class and ADI’s class.Key Words: ADI; ADI-S; scientific reasoning abilities; cognitive learning outcomesAbstrak: Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar kognitif siswa yang dibelajarkan menggunakan model Argument Driven Inquiry-Scaffolding (ADI-S) dan model Argument-Driven Inquiry (ADI) dengan kemampuan penalaran ilmiah berbeda. Rancangan penelitian yang digunakan adalah quasy eksperimental design. Instrumen yang digunakan yaitu tes hasil belajar kognitif dan tes kemampuan penalaran ilmiah. Data dianalisis menggunakan ANCOVA dua jalur (faktorial 2x2). Hasil analisis menunjukkan: (1) pembelajaran dengan model ADI-S pada materi laju reaksi memberikan hasil belajar kognitif yang lebih tinggi jika dibandingkan dengan model ADI, (2) siswa dengan kemampuan penalaran ilmiah tinggi memberikan hasil belajar kognitif lebih tinggi dibandingkan kemampuan penalaran ilmiah rendah baik pada kelas ADI-S maupun ADI.Kata kunci: ADI; ADI-S; kemampuan penalaran ilmiah; hasil belajar kognitif